THE IMPACT OF TECHNOLOGY ON MODERN TEACHING METHODS - Eshdavlatova Adiba Zafarovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: This article examines the role of technology in transforming modern teaching methods from a humanities perspective. It argues that digital tools improve educational outcomes, increase student engagement, and promote digital literacy. Platforms such as Khan Academy and Coursera support personalized learning, while Google Classroom and Zoom enhance collaboration. Although challenges such as inequality and distraction exist, responsible integration of technology creates a more effective and inclusive learning environment.